The Role of Mediation on Work Practices and Employee Involvement - Nuzulul Fatimah; Nauman Tahir; Muhammad Ali Ahmad; Amna Batool; Arbab Gul; Abid Fareed (Faculty of Economic and Business, 2021)
Organizations face many challenges regarding employee engagement and employee job satisfaction. To increase the level of employee job satisfaction, HIWP must be implemented in order to have an impact on employee performance satisfaction. The purpose of this study was to examine the relationship between high-involvement work practices (HIWP) and job satisfaction with the mediating effect of employee engagement; HIWPs consist of four main attributes: (a) power (b) information (c) reward (d) knowledge. This study investigates the relationship between the three variables. Here, convenience sampling was used and data were collected through questionnaires from 185 organizational respondents in the banking sector. Regression analysis was used to test the hypothesis and Andrew F. Hayes model 4 was used to examine the mediating effect. The results showed that there was a significant relationship between the mediating variables and the effect of employee engagement. This study expands on HIWP employment and job satisfaction. The practical implication of this research is to measure the level of job satisfaction of employees by using HIWP can be implemented for managers and employees.